DESIGNING INCARY LEARNING MEDIA IN LISTENING SKILL FOR 10TH GRADE - Yuyun Bahtiar; Rina Zunanik (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
In the world of education, language is important as a means of communication. Many languages ​​are used in the learning process, one of which is English. English consists of four skills include speaking skill, reading skill, writing skill, and listening skill. Of the four abilities, the listening ability is often considered difficult by students. The researcher conducted research at the Islamic Senior High School At-Taufiq, Diwek, Jombang. The research subjects were students in 10th grade, which consisted of 12 students. From the observations, the researcher found problems with students, namely many students felt bored with English lessons, especially during the listening section. From this problem, the researcher took a study entitled Designing INCARY Learning Media in Listening Skill for 10th grade. The purpose of this research is to create English learning media for 10th grade. The researcher uses Research and Development (R&D) research using the ADDIE model. From the results of material validation, the researcher got a score of 86.3%, while for learning media it was 88.6%, while for product implementation it got a score of 85.8%. From these results, it is included in the "Very Good" category, which means that the learning media is feasible to use.